Relationship between Knowledge and Compliance of Pregnant Women in Consuming Fe Tablets in the Work Area of the Kartasura Public Health Center - Arvinda Dwi Nugraheni; Sulastri Sulastri (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
One of the common health issues that can seriously affect both the mother and the foetus is anaemia disease in pregnant women. Taking iron (Fe) supplements on a regular basis throughout pregnancy is one way to prevent anaemia. Numerous expectant mothers in the Kartasura Health Center's service area are still unaware of the benefits of taking iron supplements during pregnancy, which leads to anaemia in many of them. In the Kartasura Health Centre, the purpose of this study is to ascertain the association between pregnant women's level of understanding on the use of Fe pills. This study employed a cross-sectional methodology and an analytical survey design. The research was conducted in the Kartasura Health Center Working Area, Sukoharjo Regency, Central Java Province, and was carried out from August 2024. The study population of pregnant women in trimesters 1-3 who were in the Kartasura Health Center Working Area was 258. The sample was taken by purposive sampling from pregnant women registered at the Kartasura Health Center, so the research sample obtained was 72 pregnant women. Data collection was done through questionnaires. Univariate analysis and the bivariate chi-square test were used to analyse the data. The results showed a significant relationship between pregnant women's knowledge level and compliance level in taking Fe tablets (p-value=0.020 < α 0.05). When it comes to taking Fe pills, pregnant women with greater knowledge are generally more obedient than those with less information. It is recommended that health workers enrich the knowledge of patients by more routinely providing education related to the need to consume Fe tablets, using leaflets or posters that are made attractive. This can be given by health workers at every pregnant women's class meeting so that the level of knowledge of mothers becomes better and they become more compliant in consuming Fe tablets. Keywords : Knowledge, Compliance, Pregnant Women, Fe Tablets, Anemia